Increased lumbar spinal column laxity due to low‐angle, low‐load cyclic flexion may predispose to acute injury. Issue 4 (28th November 2018) - Gale, Nicole C.; Zeigler, Stacey L.; Towler, Christopher; Mondal, Sumona; Issen, Kathleen A.; Mesfin, Addisu; Michalek, Arthur J.; Kuxhaus, Laurel
Abstract : Lumbar spinal column laxity contributes to instability, increasing the risk of low back injury and pain. Until the laxity increase due to the cyclic loads of daily living can be quantified, the associated injury risk cannot be predicted clinically. This work cyclically loaded 5‐vertebra lumbar motion segments (7 skeletally‐mature cervine specimens, 5 osteoporotic human cadaver specimens) for 20 000 cycles of low‐load low‐angle (15°) flexion. The normalized neutral zone lengths and slopes of the load‐displacement hysteresis loops showed a similar increase in spinal column laxity across species. The intervertebral kinematics also changes with cyclic loading. Differences in the location and magnitude of surface strain on the vertebral bodies (0.34% ± 0.11% in the cervine specimens, and 3.13% ± 1.69% in the human cadaver specimens) are consistent with expected fracture modes in these populations. Together, these results provide biomechanical evidence of spinal column damage during high‐cycle low‐load low‐angle loading. Abstract : Cervine and human cadaver lumbar motion segments were cyclically loaded in flexion to simulate a common activity of daily living of bending forward. Normalized neutral zone lengths and slopes of load‐displacement hysteresis loops, intervertebral kinematics, and surface strain on the vertebral bodies all provided biomechanical evidence of increased spinal column laxity. This high‐cycle low‐load low‐angle loading regime causes a change in motion segment behavior; future work could translate these changes into specific activity and rest recommendations to minimize injury risk.